ASSOCIATION OF LACTOFERRIN GENE POLYMORPHISM WITH MILK PRODUCTION AND COMPOSITION - & Al-Samarai, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to determine the genotypes and allele frequency of polymorphism at position +7605 in exon 4 of the goats lactoferrin gene and to quantify their association with milk production traits using 50 goats , A 430 bp product of Lactoferrin gene exon4 was amplified and the goats were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method and NlaIII restriction enzyme. The study revealed of SNP (+7605 C/T) in Lactoferrin gene exon4 and Two alleles T and C, were identified in the studied population . Their frequencies were 0.77 and 0.23, respectively. The alleles controlled the occurrence of three genotypes: TT, TC and CC with frequencies 62 , 30 and 8 %, respectively. GLM (Generalized linear Model) analysis was applied to evaluate the association between lactoferrin gene genotypes and milk production and composition. Significant association was found (P<0.05) between SNP (+7605 C/T) genotypes and milk protein; animals with the CC genotype had higher mean values for milk protein than those with the TT ,TC genotype also the same genotype had significantly higher (P < 0.05) in milk production Compared with TT genotype . Other traits did not show any significant difference. the SNP has the potential to be considered as marker-assisted selection .